Implementation of Conflict Management in the Development of Islamic Education Jember - Saihan; Sofiah (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
not only organizations, but also in the field of education there are conflicts. There is conflict in educational institutions because there are several parties involved in conflicts and gaps. Conflicts that were initially considered as negative, if managed properly can be used as competition to improve the quality of education. As well as Islamic educational institutions in Jember Regency. The purpose of this study is to analyze conflict management strategies carried out by Islamic Education institutions in Jember Regency. This research uses qualitative research with femenological approaches and sampling techniques with purposive sampling. The results explained that the conflicts that occurred in Islamic Education Institutions, especially the Jember Regency Boarding School, were Political Conflicts, Social Conflicts, Economic Conflicts and Task Conflicts. The conflict management strategy carried out is to try to prevent conflicts that occur by building good communication and carrying out good deeds between each other with various efforts, including Tabayyun, deliberation, Amar ma'ruf Nahi Munkar.